Nest Site Selection by Green Sea Turtles (Chelonia mydas) and Implications for Conservation on Qilianyu, Xisha Islands, South China Sea - Ting Zhang; Xiaoyu An; Chenglong Zhang; Yunteng Liu; Yupei Li; Yangfei Yu; Jichao Wang; Liu Lin; Hai‐Tao Shi (Ecology and Evolution)
ABSTRACT The green sea turtle (Chelonia mydas) is the only sea turtle species that breeds in China, and the largest remaining nesting grounds for green sea turtles in Chinese waters is found on the Qilianyu atoll of the Xisha Islands. Nesting site selection is particularly important for egg survival, and understanding the microhabitat characteristics of green sea turtle nesting sites is crucial for delineating priority conservation areas for nesting grounds. In this study, we aimed to examine the role of several microhabitat ecological factors in the selection of nesting sites and the success of nesting. To this end, we performed differential comparisons, principal component analysis, and generalized linear model analysis. There were significant differences in microhabitat ecological factors, such as surface temperature, humidity, and particle size distribution (0.250–1 mm), between the nesting sites and the surrounding area. Green sea turtle nests were concentrated at a distance of 20.1–30 m from the high tide line, with a preferred distance from vegetation of 0–0.5 m. The vegetation cover of successful nests was concentrated in the range of 0%–25%, and the preferred sand types for successful nests were coarse sand (0.425–1 mm) and medium sand (0.250–0.425 mm). The average hatching success of six green sea turtle nests on North Island was 94.52%. The key microhabitat factors affecting the success of nesting were found to be sand characteristics such as humidity, bulk density, and particle size ratio. Therefore, green sea turtles on the Xisha Islands exhibit preferences for microhabitat ecological factors during nesting site selection, and the ecological characteristics of nesting grounds can affect the hatching success rate of green sea turtles. Therefore, it is recommended to continuously monitor the characteristics of and changes in green sea turtle nesting site selection and take measures to provide high‐quality nesting and hatching environments for sea turtles.